Effect of geometric configuration on the laminar flow and heat transfer in microchannel heat sinks with cavities and fins. (4th March 2017) - Li, Yifan; Xia, Guodong; Jia, Yuting; Ma, Dandan; Cai, Bo; Wang, Jun
ABSTRACT: A numerical simulation is performed to investigate the characteristics of flow and heat transfer in microchannels with cavities and fins. Nine microchannels with various shaped cavities and fins are presented and compared to the smooth microchannel. The effect of cavity and fin shapes on the flow field and temperature field is analyzed. Results show that the presence of cavity and fin can increase the heat transfer area, intensify mainstream disturbance, and induce chaotic advection, which result in obvious heat transfer enhancement. The shape of cavity or fin has a great influence on the hydrodynamic and thermal performance for such micro heat sinks. Based on the performance evaluation criterion ( PEC ), the overall performance of the microchannel is evaluated. The combination of cavities and fins leads to lower bottom temperature, lower net temperature gradient of fluid, and better heat transfer performance, which has the potential to meet the increased heat removal requirement.